Blood And Its Functional Structure (Texas Journal of Medical Science, 2025)
The work examines the composition of human blood. It is shown that white cells are divided into agranulocytes and granulocytes. Lymphocytes play a decisive role in the formation of antibodies and other protective reactions. Neutrophils (70%) contain enzymes in the cytoplasm that destroy bacteria, so their accumulations are found in those areas of the body where the infection is localized. The functions of blood are much more complex than just the transport of nutrients and metabolic waste. Hormones that control many vital processes are also transported with blood; blood regulates body temperature and protects the body from damage and infection in any part of it.